ANALYSIS OF EXCEPTIONAL DECISIONS IN MEDICAL PRACTICE CRIMINAL ACTIONS: Decision No. 1441/Pid.Sus/2019/PN Mks - Sushanty, Vera Rimbawani; Huroiroh, Ernawati; Akbar, Kenza Kalihanugrah (Acitya Wisesa: Journal of Multidisciplinary Research, 2024)
Medical malpractice remains a significant legal issue, with various stakeholders, including patients, families, and doctors, facing difficulties in navigating the legal landscape. The existing laws do not comprehensively define medical malpractice, leading to confusion and inconsistent enforcement of justice in cases involving medical professionals. The purpose of this research is to analyze the legal problems associated with medical malpractice and to provide recommendations for improving the legal framework governing medical practice in Indonesia. This research aims to contribute to law enforcement in handling criminal cases related to medical malpractice and to suggest amendments to the Law of the Republic of Indonesia Number 29 of 2004 concerning Medical Practice. This research employs a normative legal research methodology, utilizing both statutory and case approaches to examine the legal issues surrounding the imposition of criminal sanctions in medical practice. The research focuses on analyzing existing laws and the decisions made by the Indonesian Medical Ethics Code Court, which often complicate investigations into medical malpractice. The findings reveal that the current legal framework inadequately protects health services, doctors, dentists, and patients in cases of medical malpractice. Investigations are frequently hindered by decisions from the Medical Ethics Code Court, which affects the legal considerations of judges in malpractice cases. The paper concludes that there is a pressing need for legal reform to enhance clarity and protection for all parties involved in medical practice.